2021
DOI: 10.1088/1361-648x/ac2388
|View full text |Cite
|
Sign up to set email alerts
|

2D–1D mixed-dimensional heterostructures: progress, device applications and perspectives

Abstract: Two-dimensional (2D) materials have attracted broad interests and been extensively exploited for a variety of functional applications. Moreover, one-dimensional (1D) atomic crystals can also be integrated into 2D templates to create mixed-dimensional heterostructures, and the versatility of combinations provides 2D-1D heterostructures plenty of intriguing physical properties, making them promising candidate to construct novel electronic and optoelectronic nanodevices. In this review, we first briefly present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…Further, 1D nanomaterials can be integrated with 2D components, serving as interconnectors or conducting channels for large‐scale integrated circuits. [ 37 ] In addition, our demonstrated simple and efficient fabrication method for mixed‐dimensional 1D/2D heterostructures can be applied to various optical structures (e.g., silicon waveguides, resonators) to improve the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…Further, 1D nanomaterials can be integrated with 2D components, serving as interconnectors or conducting channels for large‐scale integrated circuits. [ 37 ] In addition, our demonstrated simple and efficient fabrication method for mixed‐dimensional 1D/2D heterostructures can be applied to various optical structures (e.g., silicon waveguides, resonators) to improve the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, 1D atomic crystals such as nanowires (NWs), nanotubes (NTs) and nanorods (NRs) are preferable candidates for integrating with 2D materials, which will exhibit various intriguing properties, such as high optical absorption, efficient carrier separation, ultrafast charge transfer, plasmon-exciton interconversion, etc. [16][17][18] For example, Jariwala et al realized electrical control of carbon nanotube/MoS 2 p-n heterojunction photodetectors that display a concurrent spectral response in the visible and near-infrared regions with an ultrafast photodetection speed. 19 Zhang et al reported a novel type-II staggered band alignment of CuFe 2 O 4 /MoS 2 mixed-dimensional heterostructures that present a distinct enhanced acetone gas sensing response.…”
Section: New Conceptsmentioning
confidence: 99%
“…Resistive-type sensors are the most studied in gas sensors but less in solution sensors . In particular, gas sensors with 1D nanostructures on thin films have a large surface area, so that high sensing performance can be obtained. , A solution sensor with this structure can be expected to realize highly sensitive and accurate detection of analytes in liquid.…”
Section: Introductionmentioning
confidence: 99%